PENGEMBANGAN MULTIMEDIA PEMBELAJARAN MATEMATIKA PADA MATERI FUNGSI KUADRAT BERBASIS RME UNTUK SISWA SMA/MA - Agus Setiawan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
This research is a development research aimed at generating media-based mathematics instruction materials RME on Quadratic Functions of high school students / MA and know the quality of the mathematics learning CD based media expert assessment, subject matter experts and learning and 30 students of class X. The development model used is a model of procedural development, is a model which is descriptive, outlining the steps that must be followed to produce the product. This development was initiated by means of analysis Content Standard continued with a reference collection of media then drafting media, and create a learning CD. CD mathematics that have been made to the experts assessed and learning materials, media experts, and students small classes and large classes. Learning CD contains material Quadratic Functions in class X which consists of seven sections, namely: Quadratic Functions, Various Graph Quadratic Functions, Quadratic discriminant function, Quadratic Functions Develop, Designing Mathematical Model, Exercises and Simulation. This research has successfully developed a mathematics learning CDs that have quality Very Good (SB) according to expert assessment and learning materials, media experts, and 30 students of class X with a score of 168.64 out of a maximum score of 185, while the percentage of keidealannya 91.16%, so fit for use as a medium of learning. Keywords: Learning Media, RME, Quadratic Functions